Episodic ataxia and severe infantile phenotype in spinocerebellar ataxia type 14: expansion of the phenotype and novel mutations - De Michele, Giovanna; Galatolo, Daniele; Galosi, Serena; Mignarri, Andrea; Silvestri, Gabriella; Casali, Carlo; Leuzzi, Vincenzo; Ricca, Ivana; Barghigiani, Melissa; Tessa, Alessandra; Cioffi, Ettore; Caputi, Caterina; et al. (Journal of neurology, 2022)
Introduction Spinocerebellar ataxia type 14 (SCA14) is a dominantly inherited neurological disorder characterized by slowly progressive cerebellar ataxia. SCA14 is caused by mutations in PRKCG, a gene encoding protein kinase C gamma (PKCγ), a master regulator of Purkinje cells development. Methods We performed next-generation sequencing targeted resequencing panel encompassing 273 ataxia genes in 358 patients with genetically undiagnosed ataxia. Results We identified fourteen patients in ten families harboring nine pathogenic heterozygous variants in PRKCG , seven of which were novel. We encountered four patients with not previously described phenotypes: one with episodic ataxia, one with a spastic paraparesis dominating her clinical manifestations, and two children with an unusually severe phenotype. Conclusions Our study broadens the genetic and clinical spectrum of SCA14.